Validação de campo do integrative medicine attitude questionnaire (IMAQ) para uso no Brasil - Pinheiro, Leonardo de Souza e Silva (2015)
Objectives: To translate, adapt and validate a questionnaire that assesses the attitude of health area students toward Complementary and Alternative Medicine (CAM). Methods: Cross-sectional, observational and prospective study. The Integrative Medicine Attitude Questionnaire is a 29-item, 7-point Likert scale rated instrument, which was translated into Brazilian Portuguese, back-translated into English, semantically corrected and culturally adapted in order to reach its final version. Cronbach's alpha, Spearman Correlation and Ceiling/ Floor Effect were used for data analysis. Results: Among 300 eligible students, 265 were present during study invitation, 172 agreed to participate, 59.3% were female, there were no losses related to incomplete questionnaires. The analysis of the responses of the instruments resulted in Cronbach's alpha of 0.717; Spearman correlation between total and individual responses means were not significant to items 5 and 27; Ceiling Effect was detected in six items and Floor Effect in other six. Conclusion: The Brazilian Portuguese version of the instrument is valid; some items can be removed without result interference of the research. It seems that the performance of the answers to some statements was related to a certain lack of knowledge regarding Eastern therapies. Factor analysis may be the choice strategy for precisely pointing out the items to be suppressed.